VIOLATION OF THE MEDICAL CODE OF ETHICS IN DOCTOR MALPRACTICE IN THE CASE OF NASAL FILLER INJECTION ON A PATIENT (Study of Supreme Court Decision Number 233 K/Pid.Sus/2021) - Wahyu Okta; Lola Yustrisia (RADJA PUBLIKA, 2026)
The medical profession plays a vital role in safeguarding human life and health; however, not all medical practices comply with professional standards and ethical codes, leading to ethical violations and medical malpractice. Malpractice may occur in the form of misdiagnosis, non-compliance with standard operating procedures, negligence, or the absence of valid informed consent, resulting in physical and psychological harm to patients. Although regulatory frameworks such as Law Number 29 of 2004 on Medical Practice and professional oversight bodies, including the Indonesian Medical Discipline Honorary Council (MKDKI) and the Medical Ethics Honorary Council (MKEK), are in place, enforcement and patient protection remain insufficient. Health is a fundamental right of every citizen, as reaffirmed in Law Number 17 of 2023 on Health, which mandates ethical and competent medical services. This study aims to identify forms of medical ethical violations committed by physicians and to analyze their legal accountability using a normative juridical approach, with reference to Supreme Court Decision Number 233 K/Pid.Sus/2021. The study finds that serious ethical breaches may constitute medical malpractice and entail legal responsibility.